NSCA's guide to sport and exercise nutrition - Campbell, Bill I. 1975- (Human Kinetics, 2021)
"This book covers aspects of food selection, digestion, metabolism, and hydration relevant to sport and exercise performance. It teaches safe and effective ways to improve training and performance through supplementation, manipulation of macronutrient intake, proper fluid intake, and nutrient timing based on the type, intensity, and duration of activity"